TPHE-Graphene: A First-Principles Study of a New 2D Carbon Allotrope for Hydrogen Storage - Laranjeira, José A. S. [UNESP]; Martins, Nicolas F. [UNESP]; Lima, Kleuton Antunes Lopes; Cabral, Luis A. [UNESP]; Júnior, Luiz A. Ribeiro; Galvão, Douglas S.; Sambrano, Julio R. [UNESP] (American Chemical Society (ACS), 2025)
The shift from fossil fuels to renewable energy sources is essential for reducing global carbon emissions and addressing climate change. Developing advanced materials for efficient hydrogen storage enables the development of sustainable energy solutions in this context. Herein, we propose sodium-decorated TPHE-graphene as a high-performance two-dimensional material for hydrogen storage. Density functional theory calculations and molecular dynamics simulations demonstrate that TPHE-graphene exhibits dynamical, thermal, energetic, and mechanical stability. The monolayer displays metallic behavior and a high Young's modulus of 250.46 N/m. Upon sodium decoration, strong chemisorption occurs with a binding energy of -2.08 eV and minimal tendency for Na atom clustering. Hydrogen adsorption analysis reveals that each Na atom can bind up to five H2 molecules, resulting in a gravimetric storage capacity of 9.52 wt %. The calculated H2 adsorption energies range from -0.22 to -0.18 eV, falling within the ideal range for reversible adsorption under ambient conditions. These findings highlight Na-decorated TPHE-graphene as a structurally robust and efficient hydrogen storage material well-suited for future green energy applications.